Discharge of a siphon spillway under submerged exit condition. Issue 2 (27th January 2023) - Ahmed, Warda M.; Li, S. Samuel; Ramamurthy, Amruthur S.
Abstract: Flow through a siphon is difficult to predict due to inherent turbulence, separation and secondary circulation. This paper overcomes the difficulty by using advanced numerical techniques and rigorously assessing their suitability. The aim of this paper is to explore reliable numerical methods for predicting submerged siphon characteristics. Using the Reynolds-averaged Navier–Stokes equations, we predicted three-dimensional velocity, pressure and turbulence quantities. We also conducted laboratory experiments for measurements of the submerged discharge coefficient C d . The mean value of C d predicted matches the measured mean value. The numerical results show flow separation in the siphon upper leg, causing secondary flow (SF) and increasing velocity above the crest. The SF shows complicated patterns and multiple turbulent eddies and reaches a maximum relative strength as large as 16%. The relative pressure has negative values in the crest region. The profiles of predicted longitudinal velocity in the crest region resemble the theoretical solution. The numerical methods and computation strategies from this paper are useful for investigating the performance of submerged siphons of various dimensions and/or geometric configurations under a wide range of hydraulic conditions. The RNG k - ε model is more suitable than the standard k - ε model and the Realizable k - ε model for turbulence closure. HIGHLIGHTS: Submerged siphon discharge coefficient from laboratory experiments is reported. Reliable numerical methods for predicting submerged siphon characteristics are developed. Complex primary and secondary flows, flow separation and turbulent vortices are predicted. Graphical Abstract